SARS-CoV-2 nsp15 enhances viral virulence by subverting host antiviral defenses - Allen Caobi; Chia-Ming Su; Christian M. Beusch; Devin Kenney; Tamarand L. Darling; Shuchen Feng; Marc Semaan; Alan Wacquiez; Nathan L. Sanders; Ena S. Tully; Da-Yuan Chen; Monika Evdokimova; et al. (Proceedings of the National Academy of Sciences, 2025)
SARS-CoV-2 encodes numerous virulence factors, yet their precise mechanisms of action remain unknown. We provide evidence that the SARS-CoV-2 nonstructural protein 15 (nsp15) enhances viral virulence by suppressing the production of viral double-stranded (dsRNA), a potent inducer of antiviral signaling. The viral variants lacking nsp15 endoribonuclease activity elicited higher innate immune responses and exhibited reduced replication in human stem cell–derived lung alveolar type II epithelial cells, as well as in the lungs of infected hamsters. Consistently, these variants caused significantly less weight loss and mortality compared to wild-type (WT) virus in K18-hACE2 mice. Mechanistically, the cells infected with nsp15 mutants accumulated more viral dsRNA, causing enhanced stimulation of the interferon pathway. Chemical inhibition of interferon signaling dampened immune responses to nsp15 mutants and restored their replication to levels similar to the WT virus. These findings indicate that the endoribonuclease activity of nsp15 contributes to viral virulence by limiting the accumulation of viral dsRNA, thereby allowing robust replication with reduced activation of the host innate immune response.